Humoristiske bøsserier og latterens perversiteter - tilblivelse af heteroseksuel maskulinitet i skolelivet på automekanikeruddannelsen - Hansen, Rasmus Præstmann (Kvinder, Køn & Forskning, 2009)
Frisky Faggoting and the Perversity of Laughter - the Production of Heterosexual Masculinity in the School life at a Car mechanic programme.Humour is conceptualized as a subjectification in the formation of masculinity and the processes of inclusion and exclusion. The article produces knowledge about the creation of hierarchy among boys in a homosocial educational context. Inspired by British educational and youth studies and Danish poststructuralist informed empirical gender studies a theoretical perspective is established on intersections between masculinity and locally composed categories in school life. The point of empirical departure is homosocial relations among boys and between boys and teachers where a dynamic hierarchy of masculinities are produced. The article shows a dominant masculinity revolving around humour and laughter, use of sexual language, ‘disgusting' practices and desires directed at imaginary female bodies. Humour enables a play with homoerotic relations and non-heterosexual desires, but at the same time a heterosexual masculinity is valued, which eliminates and subordinates the perversions of laughter and the frisky faggoting among the boys at the Car mechanic programme.